Pengaruh motivasi belajar dan konsep diri terhadap prestasi belajar mata pelajaran matematika siswa - Ulfah Musyaropah; Nurhayati Adiratna Kusuma; Asti Iryanti Putri; Widiarti Widiarti; Yayi Tresnatri; Ahmad Muhammad Diponegoro (Psikoislamika, 2022)
Abstract: This study aims to examine the effect of learning motivation and self-concept on student achievement in mathematics at SMK Muhammadiyah 2 Sleman. This research uses a quantitative approach with a cross sectional study method. The population of this study were students of SMK Muhammadiyah 2 Sleman. The sampling technique in this study used saturated sampling. The sample in this study amounted to 40 students. The data collected by using a learning motivation scale and a self-concept scale with a Likert scale response type. Meanwhile, students' mathematic test scores used as the data of learning achievement. The data analysis technique used in this research is multiple linear regression analysis. The results showed that simultaneously there is a very significant influence between learning motivation and self-concept on student achievement in mathematics at SMK Muhammadiyah 2 Sleman. The contribution of learning motivation and self-concept to student achievement is 63,4%. The implication of this research is to Give an information that the student study motivation is important to be improved to boost the student study performance.